HPV infection and carcinogenesis in the upper aero-digestive tract (Colombia Medica, 2011)
Recently, molecular and epidemiological studies have shown an etiologic role for human papillomavirus (HPV) in a subset of upper aero-digestive tract (UADT) cancers in women and men. Oral HPV infections acquired through oral sex seems to be the main risk factor for HPV-associated oral cancers. The high-risk type HPV-16 was the most prevalent infection HPV-positive in most oral cancers. Therefore, the prophylactic vaccine against HPV-16 could prevent HPV associated oral cancer if the vaccine were demonstrated to be capable of preventing oral HPV-16 infection. Thus, these findings have created new potential opportunities for the primary prevention of oral cancers.